A case of central mucoepidermoid carcinoma associated with dentigerous cyst - Sayed Mohammad Razavi; Roya Yahyaabadi; Saeedeh Khalesi (Wolters Kluwer Medknow Publications, 2017)
Mucoepidermoid carcinoma (MEC) is the most common malignant salivary gland neoplasm. Central MEC (CMEC) is a rare primary intraosseous bony lesion with an incidence of 2%-4.3% of all MECs reported. In this article, we present a rare case of a CMEC in the anterior region of maxilla at a 43-year-old female patient that was arising from a dentigerous cyst. CMECs are extremely rare tumor. They are usually low-grade lesions with favorable prognosis. Odontogenic cysts are one of the origins of this lesion. Treatment of impacted tooth is necessary in the early stage for prevention of this neoplasm.